IDENTIFYING OF FAKE NEWS: THE IMPORTANCE OF DIGITAL LITERACY (International Conference on Social and Islamic Studies, 2022)
Living in Indonesia with its diversity of cultures, ethnicities, religions and other diversity demands high tolerance and mutual respect from every citizen. This long-standing diversity must be maintained and preserved. However, recently, with the unstoppable spread of massive information, this long-established relationship has begun to crack. Fake news, including hoaxes, has filled these diversity spaces, and not a few have attempted to create social conflict. This paper attempts to find out in general how fake news is formed and spread. But most importantly, this paper will offer tips on identifying fake news. This literature research is a continuation of previous research where the data source was obtained from the results of capturing fake news that had been published on online media and social media. The results of the study show that the dissemination of fake news begins with creating information adopted from public opinion, it was then formed into articles, flavored with false sentences, and spread via social media using anonymous accounts, so that people who read it spread it back to other communities and so on. Fake news can ruin a good relationship if each party does not verify and confirm information. Thus, digital literacy plays an important role to identify fake news.